P3-S6.06 Does the concept of early and late latent syphilis hold well in today's scenario?. (10th July 2011) - De, D; Kanwar, A
Abstract : Background: Latent syphilis refers to the asymptomatic stage in the natural evolution of syphilis in a patient not treated or inadequately/inappropriately treated for syphilis. Latent syphilis has been categorised as early latent and late latent for therapeutic purposes. Indiscriminate and inadequate over the counter use of antibiotics (happenstance) and HIV co-infection in present day scenario tends to change natural evolution of syphilis. Even though some patients remain asymptomatic without any historical evidence of clinical manifestation of syphilis, serologically they continue to reflect the ongoing infection process; the so called syphilis of unknown duration. Objective: To determine the sero-epidemiological characteristics of patients with syphilis of unknown duration registered to a sexually transmitted disease (STD) clinic in an Institute setting. Patients and Methods: Clinic records of patients registered to the STD clinic between 2006 and 2010 were retrieved. For study purposes, syphilis of unknown duration was defined as positivity with Treponema Pallidum Haemagglutination assay (TPHA) irrespective of Venereal Disease Research Laboratory (VDRL) titre in patients who did not have any clinical sign of syphilis including neurological and cardiac, during clinic entry; had no features to suggest syphilis in the past and had not been treated with parenteral penicillin. Results: Of the 76 patients registered during the study period, 52 (68%) satisfied the diagnosis of syphilis of unknown duration. Age of patients was between 20 and 56 years (mean 29.76, standard deviation 8.32). Males outnumbered females by a ratio of 2.25:1. Majority (33, 63.4%) of the patients were direct walk-in with positive serology results done in private laboratories, mostly in patients who are habituated to unprotected extramarital sexual intercourse. Others were referred from obstetric clinics (15.4%), private practitioners (15.4%), HIV clinic (1.9%), transfusion medicine (1.9%) and urology clinic (1.9%). Majority patients (31, 59.61%) showed low titre VDRL (upto 1:8) positivity while 5 (9.6%) were VDRL non-reactive. Conclusion: In majority of syphilis patients, duration of latency could not be determined due to lack of history of clinical lesions of early syphilis or reliable history of time of acquisition of infection. Consequently, the categorisation of latent syphilis to early and late phases in present day scenario appears redundant.